A New Cyclic Hexapeptide and a New Isocoumarin Derivative from the Marine Sponge-Associated Fungus Aspergillus similanensis KUFA 0013 - Chadaporn Prompanya; Carla Fernandes; Sara Cravo; Madalena M. M. Pinto; Tida Dethoup; Artur M. S. Silva; Anake Kijjoa (Marine Drugs, 2015)
A new isocoumarin derivative, similanpyrone C (1), a new cyclohexapeptide, similanamide (2), and a new pyripyropene derivative, named pyripyropene T (3) were isolated from the ethyl acetate extract of the culture of the marine sponge-associated fungus Aspergillus similanensis KUFA 0013. The structures of the compounds were established based on 1D and 2D NMR spectral analysis, and in the case of compound 2 the stereochemistry of its amino acid constituents was determined by chiral HPLC analysis of the hydrolysate by co-injection with the d and l amino acids standards. Compounds 2 and 3 were evaluated for their in vitro growth inhibitory activity against MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and A373 (melanoma) cell lines, as well as antibacterial activity against reference strains and the environmental multidrug-resistant isolates (MRS and VRE). Only compound 2 exhibited weak activity against the three cancer cell lines, and neither of them showed antibacterial activity.